A case study on the public relations of Bulacan Provincial Library - Esguerra, Ma. Carmela C.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
Public relations is one aspect of librarianship that is always taken for granted by many libraries particularly the public ones. Thus, the purpose of this study was to discover how the Bulacan Provincial Library promotes itself and how effective its strategies are, since it is the biggest public library that exists in the province of Bulacan with rich collections and services offered to its clientele and to other residents of Bulacan.
This research study aimed to: 1) find out if Bulacan Provincial Library has an existing PR program; 2) know the strategies being implemented by the Bulacan Provincial Library; 3) know the person in charge or responsible in handling the implementation of the strategies; 4) know how effective their strategies are; and 5) cite the problems that they encountered and might encounter in implementing the strategies.
This research study aimed to: 1) find out if Bulacan Provincial Library has an existing PR program; 2) know the strategies being implemented by the Bulacan Provincial Library; 3) know the person in charge or responsible in handling the implementation of the strategies; 4) know how effective their strategies are; and 5) cite the problems that they encountered and might encounter in implementing the strategies. This study hypothesized that: the clientele's awareness of the existence of the Bulacan Provincial Library depends on the public relations program being implemented by the librarian. The study followed the case study method. The subjects were the chief librarian, the former librarian, the staff, and a random sampling of clientele. Questionnaires and interviews were the main instruments used.
The data gathered revealed that Bulacan Provincial Library has no PR program but uses strategies in promoting the library's collections and services such as; annual reports, library orientations, exhibits and displays, library publications, press/news releases
Vita.
Computer print out.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Public relations -- Libraries -- Philippines -- Bulacan; Public libraries -- Philippines -- Bulacan -- Case studies; Bulacan Provincial Library